2010
DOI: 10.1007/s00371-010-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

SkelTre

Abstract: Terrestrial laser scanners capture 3D geometry of real world objects as a point cloud. This paper reports on a new algorithm developed for the skeletonization of a laser scanner point cloud. The skeletonization algorithm proposed in this paper consists of three steps: (i) extraction of a graph from an octree organization, (ii) reduction of the graph to a skeleton, and (iii) embedding of the skeleton into the point cloud. For these three steps, only one input parameter is required. The results are validated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 22 publications
1
58
0
1
Order By: Relevance
“…Imperfections of the merged point cloud, caused by remaining registration errors, noise or i.e., moving branches which were influenced by wind, are overcome in most cases because of the digitization method ( Figure 11). This is an advantage compared to voxel methods, which are based on a merged pointcloud e.g., [15,16,18]. One of the big benefits of using single scans and their projections is that the inevitable systematic errors (imperfect registration) and random errors (noise) are an unsolvable problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imperfections of the merged point cloud, caused by remaining registration errors, noise or i.e., moving branches which were influenced by wind, are overcome in most cases because of the digitization method ( Figure 11). This is an advantage compared to voxel methods, which are based on a merged pointcloud e.g., [15,16,18]. One of the big benefits of using single scans and their projections is that the inevitable systematic errors (imperfect registration) and random errors (noise) are an unsolvable problem.…”
Section: Discussionmentioning
confidence: 99%
“…Based on TLS voxel data, Bucksch [17,18] derives the center of gravity of TLS points within each voxel to finally connect these points to a graph. To ensure that outliers or noise do not alter the graph erroneous voxels are eliminated by applying a robust test.…”
Section: Related Workmentioning
confidence: 99%
“…A partir da análise de grafos formados pela conectividade das células e de suas principais direções cartesianas, Bucksch et al (2010) propuseram o método SkelTre para reconstrução da árvore em tronco e galhos.…”
Section: Introductionunclassified
“…Especially, terrestrial laser scanning (TLS) has been demonstrated as a very effective tool in measuring tree/stand properties not directly measurable which are of interest in forest research, such as crown displacement (Seidel et al 2011b), competition among trees (Metz et al 2013), leaf area distributions (Béland et al 2011) or crown volume and surface (Metz et al 2013). Furthermore, a detailed assessment of branch dimensions became possible by means of 3D-TLS (Bucksch et al 2010, Dassot et al 2012). …”
Section: Introductionmentioning
confidence: 99%